(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
A The most important question of our study is to find out what pension policy procedures are necessary to effectively respond to the challenges of an aging population as well as changes in the composition of employees. The main issue of our paper is how pension policy can effectively respond to changes of demographical transition. It is very important to examine whether changes to pension policy are adapted to groups in society and if so, what means of communication should be used. Our research is the pilot study of research of a greater scope. We examine the characteristics and communication practices of pension reforms in international literature (secondary research), and we also use primary methods (interviews, surveys). This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.